2022
DOI: 10.1111/trf.17146
|View full text |Cite
|
Sign up to set email alerts
|

Association between isolated abnormal coagulation profile on transfusion following major surgery: A NSQIP analysis of individuals without bleeding disorders

Abstract: Introduction: Preoperative coagulation screening for patients without bleeding disorders remains controversial. The combinatorial risk of INR, aPTT, and platelet count (PLT) abnormalities leading to bleeding requiring transfusion is not known in these patients. We examined the association between abnormal coagulation profile and the risk of transfusion following common elective surgery in patients without bleeding disorders. Study Design and Methods: We utilized the National Surgical Quality Improvement Progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…First of all, we are delighted about the interest of Baykara et al's group of authors on our novel purification procedure for granulocyte concentrates (GC). 1 So far, the therapeutic use of GC has been reserved for distinct indications. Clinical applicability and usability were limited due to the rapid deterioration in quality caused by enormous lactate production by copious amounts of erythrocytes, resulting in a severely low pH within the first 24 h. The new purification procedure provides multiple advantages by removing contaminations of erythrocytes, platelets and sedimentation agents, thereby providing better storage conditions for leukocytes as well…”
Section: Funding Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, we are delighted about the interest of Baykara et al's group of authors on our novel purification procedure for granulocyte concentrates (GC). 1 So far, the therapeutic use of GC has been reserved for distinct indications. Clinical applicability and usability were limited due to the rapid deterioration in quality caused by enormous lactate production by copious amounts of erythrocytes, resulting in a severely low pH within the first 24 h. The new purification procedure provides multiple advantages by removing contaminations of erythrocytes, platelets and sedimentation agents, thereby providing better storage conditions for leukocytes as well…”
Section: Funding Informationmentioning
confidence: 99%
“…on the association between preoperative coagulation tests and perioperative red blood cell (RBC) transfusion. 1 This retrospective analysis included 672,075 elective major surgical cases that occurred between 2004 and 2018 using the National Surgical Quality Improvement Program (NSQIP) database.The authors hypothesized that isolated or combined abnormalities in the international normalized ratio (INR), activated partial thromboplastin time (aPTT), and platelet count (PLT) before surgery would be associated with increased bleeding and subsequent RBC transfusions.An adjusted odds of transfusion was increased by 5-fold in the cases with all three test abnormalities compared to the group with normal results. While the clinical implications of preoperative coagulation tests were elegantly discussed in the accompanying editorial, 2 we would like to further comment on the analytical issues relating to the large multi-specialty data across many years.First, the study patients were identified across 10 surgical specialties with heterogeneous procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Transfusion , Lim and colleagues report a retrospective cohort analysis of the association between preoperative coagulation studies and perioperative bleeding risk 1 . The paper describes the largest cohort studied to date on this topic: more than 600 000 non‐trauma surgeries from the American College of Surgeons' National Surgical Quality Improvement Project (NSQIP) database.…”
Section: Cutoff Sensitivity (%) Specificity (%) Ppv (%) Npv (%) Auroc...mentioning
confidence: 99%
“…In this issue of Transfusion, Lim and colleagues report a retrospective cohort analysis of the association between preoperative coagulation studies and perioperative bleeding risk. 1 The paper describes the largest cohort studied to date on this topic: more than 600 000 non-trauma surgeries from the American College of Surgeons' National Surgical Quality Improvement Project (NSQIP) database. A relationship of blood loss with burden of surgical injury and reduced coagulation capacity is logical and strongly present following severe injury but had been seen only occasionally in previous smaller studies of elective surgery.…”
mentioning
confidence: 99%